TUAN GURU DALAM PUSARAN KONTESTASI POLITIK DI LOMBOK TENGAH (STUDI MOTIF DAN AKSI POLITIK) - Amrillah, Muhammad (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2021)
Tuan guru's character in the Lombok Community encourages Tuan Guru to be involved in practical politics so that it has an impact on da'wah activities. This study uses a descriptive qualitative approach, data collected by the method of observation, documentation and interviews. This study resulted in a fact that the involvement of the guru - Tuan Guru in Praya Subdistrict, Central Lombok in politics was motivated by their capacity and role in society, but then the role shifted towards "political oriented". The role of the teacher is no longer only as a preacher but shifts as a practical political actor who is feared to make da'wah as an opportunity to carry out political socialization that is full of political interests. The reasons for the teacher to enter into practical politics are: Channeling aspirations in the community, develop Islamic institutions, enforce the commandments of good and evil, building political participation and education for the community.